2015
DOI: 10.25045/jpis.v06.i2.09
|View full text |Cite
|
Sign up to set email alerts
|

Security Trends in Modern Computer Networks

Abstract: SECURITY TRENDS IN MODERN COMPUTER NETWORKSThe article analyses the trends in the security of computer networks (CNs). The trends in the infrastructure, applications and usage of CNs are analysed. The effects of these trends on CN security are analysed. This paper finds that the determination of CN security trends can help uncover new security threats and deal with them effectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 1 publication
0
0
0
Order By: Relevance
“…In addition, when designing new WiFi networks, the density of WiFi channels and the number of users should be taken into account [3,9].…”
Section: Solution Of the Problemmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, when designing new WiFi networks, the density of WiFi channels and the number of users should be taken into account [3,9].…”
Section: Solution Of the Problemmentioning
confidence: 99%
“…The main danger of the wireless network is the harm it can cause to human health [8][9][10]. Although it was previously thought that Wi-Fi networks had no adverse health effects, studies have shown otherwise.…”
Section: Solution Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation